2020
DOI: 10.1021/acs.jafc.0c02122
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antidiabetic Activities of Flavonoid Derivatives from the Outer Skins of Allium cepa L.

Abstract: The onion, known as the bulb onion or common onion, is not only a key ingredient in many tasty and healthy vegetarian meals but also many traditional medicines. Nine new flavonoids [cepaflavas A, B (5, 6), cepadials A−D (7−9 and 14), and cepabiflas A−C (10−12)] and six known compounds (1−4, 13, 15) were obtained from the outer skins of Allium cepa L. Among them, compounds 5, 6, and 9 might be artificial products formed during extraction and isolation. New compounds were structurally elucidated using various sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 35 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…Diabetes is a progressive metabolic disorder that affects the heart, blood vessels, skin, kidneys, and nerves and may lead to serious medical conditions such as heart attack, kidney failure, blindness, and stroke [ 97 ]. According to WHO datasheet, globally around 422 million people are diagnosed with diabetes, and it is solely responsible for 1.6 million deaths per year.…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is a progressive metabolic disorder that affects the heart, blood vessels, skin, kidneys, and nerves and may lead to serious medical conditions such as heart attack, kidney failure, blindness, and stroke [ 97 ]. According to WHO datasheet, globally around 422 million people are diagnosed with diabetes, and it is solely responsible for 1.6 million deaths per year.…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“…For this reason, scientists are looking at natural resources such as medicinal plants as alternative therapeutic agents against diabetes, as they are less harmful and have a lot of pharmacological value [ 98 , 99 ]. At present, many studies [ 97 , 98 , 100 ] are being performed on A. cepa to investigate its antidiabetic activities, and one of the experiments which was tested on diabetic rats showed that the aqueous extract of onions reduced blood glucose level in the same manner as that of glibenclamide, a conventional antidiabetic drug. The results also reported that the onion extracts contained kaempferol-3-O- β -D-6 ( P- coumaroyl) glucopyranoside which is responsible for the antidiabetic effect by promoting glucose uptake in rat soleus muscle [ 101 ].…”
Section: Therapeutic Potential Of Allium Cepamentioning
confidence: 99%
“… 38 - 40 Flavonoids are secondary derivative that incorporates around 4500 recognized components. 41 The beneficial effects of flavonoids on wellbeing have been long-established for its antidiabetic, 42 anticancer, 43 antioxidant, 44 and anti-inflammatory activities. 45 A preceding study of Nepote et al 46 recommended that methanol solvent is best for the different phenolic contents extraction.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of silibinin was downloaded from Chemspider (). To obtain the most stable geometry, the ligand structure (silibinin) was optimized using the B3LYP hybrid density functional theory (DFT) employing the 6-31G* basis set and quantum chemistry software Gaussian 09W . Molecular docking was performed on the AutoDock 4.2 program.…”
Section: Methodsmentioning
confidence: 99%